Diabetes in Sub-Saharan Africa: Kenya, Mali, Mozambique, Nigeria, South Africa and Zambia - Azevedo, Mario (Medknow Publications, 2008)
Until a few years ago, a limited number of epidemiologists or public health experts mentioned the words “diabetes.” As new lifestyles, imported dietary practices, and globalization take roots in the developing world, as Africa is, today, diabetes and its complications are considered an epidemic in Africa, compelling African governments to start paying more attention to its impact as thousands of Africans run the risk of dying young. The potential severity of diabetes is such that some epidemiologists predict that its economic impact and death toll will surpass the ravages of HIV and AIDS in the near future. On the African sub-continent, present literature and the work of the World Diabetes Foundation have highlighted three countries, namely, Mali, Mozambique, and Zambia. However, the conditions in South Africa, Kenya, and Nigeria, some of the most developed areas of the continent, provide a clue to how people are coping and how governments are responding to diabetes and its full impact. This study is, therefore, a meta-summary of the incidence and prevalence of today's emerging silent killer or diabetes in Sub-Saharan Africa. The theme is that time is running out for Africa and that, as was for HIV/AIDS, by the time the governments wake up and stop denying the catastrophic potential of the epidemic, diabetes will simply overwhelm the continent's resources, and the world will witness the death of millions of Africans. The last section is a call for action against diabetes in terms of advocacy, promotion of awareness, and public health policies that empower people to diabetes self-management.